2006
DOI: 10.3109/10929080601090516
|View full text |Cite
|
Sign up to set email alerts
|

Implant position calculation for acetabular cup placement considering pelvic lateral tilt and inclination

Abstract: Using computer navigation, it is possible to determine pelvic inclination and lateral tilt during an operation by calculating the angular difference between the anatomic frontal plane and the "real world" frontal plane (i.e., the OR table). This method may be helpful in increasing the accuracy of positioning of acetabular cups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…22 It has been shown that pelvic orientation changes according to the position of the patient 23,24 and induces variations in anteversion of the acetabular component. 25 Pelvic orientation has recently been reported to change after THR, generating errors of up to 20° for measurement of anteversion. 26 This variable is eliminated by 3D planning, as the unwanted pelvic rotations are removed and the planning performed in the ante-rior pelvic plane.…”
Section: Discussionmentioning
confidence: 99%
“…22 It has been shown that pelvic orientation changes according to the position of the patient 23,24 and induces variations in anteversion of the acetabular component. 25 Pelvic orientation has recently been reported to change after THR, generating errors of up to 20° for measurement of anteversion. 26 This variable is eliminated by 3D planning, as the unwanted pelvic rotations are removed and the planning performed in the ante-rior pelvic plane.…”
Section: Discussionmentioning
confidence: 99%
“…most CAN systems require highly accurate intraoperative registration of bony landmarks (within millimeters) (17), firm placement of fiducials or tracking markers, and use the FPP to report angulation of the cup (5,18). Several authors have recognised that use of the FPP without consideration of the RWP is problematic in the 15% of patients with pelvic tilt greater than 10° and that real world cup anteversion decreases by 0.7-0.8° for every 1° of pelvic inclination (forward or lordotic tilt) (5,16,(19)(20)(21). Cup abduction, in comparison, is relatively consistent regardless of pelvic tilt (20).…”
Section: Defining Abduction and Anteversionmentioning
confidence: 99%
“…Several authors have recognised that use of the FPP without consideration of the RWP is problematic in the 15% of patients with pelvic tilt greater than 10° and that real world cup anteversion decreases by 0.7-0.8° for every 1° of pelvic inclination (forward or lordotic tilt) (5,16,(19)(20)(21). Cup abduction, in comparison, is relatively consistent regardless of pelvic tilt (20).…”
Section: Defining Abduction and Anteversionmentioning
confidence: 99%
“…In THA an accurate alignment and exact positioning of the hip prosthesis is a major factor affecting the longevity of a hip implant [7,8]. The hip joint is one of the most important weight-bearing joints in the human body, and it has an important biomechanical function: it enables a physiological bi-pedal gait and mobility, respectively, for a lifetime.…”
Section: Introductionmentioning
confidence: 99%